Design and Analysis of QoS Routing Framework integrated with OLSR protocol for Multimedia Traffic in Mobile Adhoc Networks - Soni, S.; Shah, J. S. (Engineering, Technology & Applied Science Research, 2017)
MANETs (Mobile Ad-hoc Networks) is the self organizing wireless structure of mobile hosts. Wireless media is used for communication in MANETs. Considering the developing requirements for multimedia and real-time traffic applications in real world, QoS (Quality-of-Service) support is essential in MANETs. But most of the characteristics of MANETs make QoS support a difficult problem. It is challenging to support QoS routing in MANET due to dynamic behavior and mobility of the hosts. The OLSR (Optimized Link State Routing) protocol can be efficiently used in MANETs to provide QoS routing because of its dynamic MPR (Multi Point Relay) selection criteria and proactive nature. In this paper, a design of QoS routing framework integrated with OLSR protocol is proposed and also analyzed using network simulator. Proposed QoS framework combines a bandwidth estimation algorithm with explicit resource reservation, QoS routing and connection admission control (CAC). OLSR protocol is extended for QoS framework to solve performance issues related to node mobility using cross layer approach. Results after simulation conclude about efficiency of the proposed QoS routing framework.